Faktor-Faktor yang Menghambat Pelayanan Penerimaan Pasien Rawat Jalan - Niska Salsiani Sinta; Wahyu Sulistiawan (Jurnal Sains & Kesehatan, 2022)
Registration service is one of the most important factors in the activities in the hospital, which is the beginning of the patient getting a good or bad impression of the services provided by all health workers in the hospital. The path consists of Man, Machine, Money, Material, and Method. This research was conducted in the medical record unit for receiving RJ patients at the Buton District Hospital. This type of research uses a descriptive research design with a qualitative study approach. The subjects in this study were patient registration officers, head of medical records and patients. The object of this research is the factors that hinder the service of receiving RJ patients. The data collection methods used were observation and interviews. Based on the results of the study, there were 13 medical record officers with details of 5 officers who graduated from medical records and 8 others including public health graduates. The machines used are still lacking, there are no queuing machines, loudspeakers, network access that is still not running well, and generators that are always damaged so that when a light goes out, the service will be stopped. The allocated funds are still very less. The materials used are sufficient, however, in making KIB it is still done manually. There is no SOP for accepting outpatients.The Man, Machines, Money, Material, Method still hinder the outpatient admission service.